Architectural design research: Drivers of practice. (4th July 2022) - Aydemir, Ayşe Zeynep; Jacoby, Sam
Abstract: Research, professional practice, and learning in architecture are becoming increasingly integrated as the understanding of research and practice is transforming and research assessment criteria are expanding. This changing research landscape has created more diverse iterative and cyclical design research processes and opened new areas of exploration and experimentation in architecture. Building on existing tripartite design research models, such as research 'into', 'for', and 'through' or research stages of 'processes', 'products/outcome', and 'performance/impact', this paper uses the concepts of 'process-driven', 'output-driven', and 'impact' to analyse and classify current architectural design research practices. This framework is used to clarify how research criteria are differently understood in academia and practice, explore the challenges arising from translation between them, and analyse the methods commonly used. While focusing on the UK context, the paper offers transferable insights while using some international case studies.